2012
DOI: 10.4103/2230-8210.103007
|View full text |Cite
|
Sign up to set email alerts
|

Congestive heart failure in acromegaly: A review of 6 cases

Abstract: Background:Though cardiac involvement is common in acromegaly, overt congestive heart failure is uncommon.Materials and Methods:This is retrospective analysis of hospital record between 1996 and 2007. We analyzed records of 150 consecutive patients with acromegaly. We included the patients with acromegaly those who had overt congestive heart failure either at presentation or during the course of illness for the present analysis. The diagnosis of acromegaly and congestive cardiac failure were based on standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…In a study performed in India, six of 150 patients (4%) with acromegaly presented with overt CHF. The authors concluded that GH and IGF-1 were the causes of the myocardial hypertrophy, because the cardiac manifestations reversed after GH and IGF-1 levels were normalized [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study performed in India, six of 150 patients (4%) with acromegaly presented with overt CHF. The authors concluded that GH and IGF-1 were the causes of the myocardial hypertrophy, because the cardiac manifestations reversed after GH and IGF-1 levels were normalized [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recordemos que la principal causa de morbimortalidad a nivel cardiovascular en este grupo de pacientes es por efecto del exceso circulante de GH; ya que provoca hipertrofia de ventrículo izquierdo, disfunción sistólica y diastólica, enfermedad valvular y cardiopatía isquémica [10]. La monitorización de rutina como electrocardiograma, frecuencia cardíaca, saturación de oxígeno, dióxido de carbono tidal final y monitoreo de presión arterial no invasivo al momento de la inducción nos puede dar información de los cambios hemodinámicos y ventilatorios.…”
Section: Discussionunclassified
“…According to a retrospective study by Khan et al [51] on the prevalence of comorbidities in patients with acromegaly, while many studies reported arrhythmias, none of the patients in their own study had a rhythm disorder [61]. In a case series by Dutta et al [61] on acromegaly with overt congestive HF, 50% of the patients died from ventricular arrhythmias, attributed to abnormal ventricular remodeling. Another case study by Subramnaian et al [62] illustrated that idiopathic premature ventricular contraction (PVC) and ventricular tachycardia (VT) can be manifestations of any systemic disease, including acromegaly.…”
Section: Arrhythmia In Acromegalymentioning
confidence: 96%
“…Mortality in acromegaly may be attributed to arrhythmias and sudden cardiac death [59], although not much is known as of writing since these aspects of CVD are less studied in acromegaly [60]. According to a retrospective study by Khan et al [51] on the prevalence of comorbidities in patients with acromegaly, while many studies reported arrhythmias, none of the patients in their own study had a rhythm disorder [61]. In a case series by Dutta et al [61] on acromegaly with overt congestive HF, 50% of the patients died from ventricular arrhythmias, attributed to abnormal ventricular remodeling.…”
Section: Arrhythmia In Acromegalymentioning
confidence: 99%
See 1 more Smart Citation